Dysphasia and Phantosmia as First Presentation of Multifocal Cerebral Anaplastic Astrocytomas. Issue 20 (May 2015) - Kong, Xiangyi; Wang, Yu; Liu, Shuai; Lu, Zhaohui; Wu, Huanwen; Mao, Xinxin; Cheng, Xin; Gao, Jun; Guan, Jian; Yang, Yi; Li, Yongning; Xing, Bing; et al.
<x xml:space="preserve">Abstract</x> Abstract Multifocal cerebral gliomas (MCGs) represent approximately 10% of gliomas and are frequently mistaken as metastases of an unknown primary cancer site. Most MCGs are glioblastomas with <4 lesions supratentorially, and are lack of typical symptoms and special detections. Through a rare MCG case, we aim to present this rarity and emphasize the need to correctly diagnose multiple intracranial lesions using a variety of diagnostic modalities to ensure that the patient receives proper treatment. We present a case of multifocal cerebral anaplastic astrocytomas with a total of 8 lesions located in the left frontal lobe and invading the lateral ventricle, presenting with dysphasia and phantosmia. The disease course, including diagnosis and treatment, is presented and analyzed in detail. The pertinent literature is reviewed regarding this uncommon entity. After an initial impression of brain metastasis from lung cancer because of the magnetic resonance imaging (MRI) resemblance and history of chronic bronchitis, we were able to use positron emission tomography (PET) and excisional biopsy to get the final diagnosis. After 10 months, the patient's overall condition deteriorated and succumbed to his disease. MCGs are easy to be misdiagnosed as metastatic diseases. In addition to MRI, PET adds more biochemical and molecular information and is helpful in the differentiation. Although uncommon, if multiple lesions are present in various locations in the hemispheres, MCG should be kept in mind.